2002
DOI: 10.1027//0227-5910.23.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Suicide Attempts in Ankara in 1998: Results of the WHO/EURO Multicentre Study of Suicidal Behaviour

Abstract: Male sex is a risk factor for completed suicide and female sex is a risk factor for attempted suicide, while an age of 15-24 years may be a risk factor for both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
3
15
1
9
Order By: Relevance
“…The overall total rate and the age-specific rates for women aged 30 years and above in this study were relatively low. These rates are comparable to the rates found in the WHO/ EURO multicentre study of parasuicide for German women in Wü rzburg, (99.9/100,000 persons) [29] and for women in Ankara, Turkey (85.6/100,000 persons) [16,28]. However, the overall suicide attempt rates were lower than the rates reported in other Turkish immigrant populations in Europe: for example, Burger et al in 2009 reported a suicide attempt rate of 221.3/100,000 person-years in Turkish females in The Hague for the years 2002-2004, and Yilmaz and Riecher-Rö ssler in 2012 reported rates between 267.4-322.4/100,000 persons in a study examining suicide attempts presenting at the emergency department of the University Hospital Basel from 1991-1997.…”
Section: Discussionsupporting
confidence: 84%
“…The overall total rate and the age-specific rates for women aged 30 years and above in this study were relatively low. These rates are comparable to the rates found in the WHO/ EURO multicentre study of parasuicide for German women in Wü rzburg, (99.9/100,000 persons) [29] and for women in Ankara, Turkey (85.6/100,000 persons) [16,28]. However, the overall suicide attempt rates were lower than the rates reported in other Turkish immigrant populations in Europe: for example, Burger et al in 2009 reported a suicide attempt rate of 221.3/100,000 person-years in Turkish females in The Hague for the years 2002-2004, and Yilmaz and Riecher-Rö ssler in 2012 reported rates between 267.4-322.4/100,000 persons in a study examining suicide attempts presenting at the emergency department of the University Hospital Basel from 1991-1997.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to various studies demonstrating a higher proportion of female suicide attempters (Sayil and Devrimci-Ö zguven 2002;Tezcan et al 1995;Zoroglu et al 2003;Saginc et al 2000;Yesil et al 2008;Ö zdel et al 2009;Yalaki et al 2011;Nock et al 2008;Beautrais et al 2006), we observed a similar proportion of male and female suicide attempters.…”
Section: Resultscontrasting
confidence: 76%
“…Case fatality has been estimated at 70-90% for different violent methods, such as firearm, hanging, or railway suicidal behavior (Erazo, Baumert, & Ladwig, 2005;Gunnell, Bennewith, Hawton et al, 2005;Miller, Hemenway, & Azrael, 2004), compared with an estimated 13% for all types of suicidal behavior (Miller, Hemenway, & Azrael, 2004). Furthermore, other studies have shown that violent methods were more common among fatal suicidal acts and nonviolent methods among nonfatal acts (Birkhead, Galvin, Meehan et al, 1993;Nishimura, Shiori, Nushida et al, 1999;Salib, & Tadros 2000;Sayil, & Devrimci-Ozguven, 2002;Van Casteren, Van Der Veken, Tafforeau et al, 1993). Finally, a correlation has been demonstrated between the use of a violent method in carrying out a suicide attempt, and later suicide (Gibb, Beautrais, & Fergusson, 2005;Hawton, 1992;Holley, Fick, & Love, 1998).…”
Section: Introductionmentioning
confidence: 95%